Child Marriage Challenges and Institutional Countermeasures: Exploring Factors, Impacts, and Government Strategies in Islamic Context - Nabila Khoirunnisa Harliani; Elmahda Nabiilah (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2026)
Child marriage has shifted from a social phenomenon into a normalized community practice, creating a stark distinction and paradox with Islamic values that emphasize human welfare (maslahat al-ummah) and the protection of future generations (hifzh al-nasl). This practice also directly hinders the achievement of the Sustainable Development Goals (SDGs), particularly Gender Equality and No Poverty. This study aims to identify the driving factors of early marriage and analyze the strategic role of the regional government as the authorized guardian (ulil amri) in mitigating its negative impacts to build a resilient society. Using a descriptive qualitative approach, data were gathered through in-depth interviews with key stakeholders (Population control and family planning Office, public health Office, and the Office of Religious Affairs in Empat Lawang Regency), participatory observation, and focus group discussions. The findings indicate that the normalization of child marriage is driven by social constructs that view early marriage as an instant remedy for low educational attainment, poverty, lack of parental supervision, and out-of-wedlock pregnancies. There is a stark distinction between the community's cultural justification and true Islamic principles; public misinterprets early marriage as a moral shield, whereas Islam substantively warns against creating a